Association between shortened maternal and fetal telomere length and abnormal fetal development - Océane Coudrieu; Zangbéwendé Guy Ouedraogo; Denis Gallot; Amélie Delabaere; Lauren Veronese; Eleonore Eymard-Pierre; Andrei Tchirkov; Carole Goumy (PLoS ONE, 2025)
A number of intrinsic, maternal and environmental factors have been linked to the risk of fetal developmental anomalies. In a previous study, we showed that telomere length (TL) was notably reduced in amniotic fluid when the fetus exhibited a developmental anomaly. In this new study, we measured the fetal and maternal TL for 75 evolutive pregnancies with congenital malformation. We also measured the TL of 50 pregnant women without fetal anomalies and 50 non-pregnant control women who had at least one child with normal development. In fetal samples, telomeres were significantly shortened in cases with congenital anomalies compared to controls (n  =  93) (P  <  0.0001). Interestingly, age-adjusted maternal TL was also significantly reduced in these cases (P  <  0.01). Receiver operating characteristic (ROC) analysis showed that maternal TL, at the optimal cut-off value, identified cases of congenital anomalies with 92% specificity and 73% sensitivity. In addition, fetal and maternal TL were correlated, with 15% to 38% of the variance in fetal TL attributable to maternal TL. Telomere shortening can lead to increased sensitivity to various maternal exposure factors and may contribute to compromised organogenesis, possibly due to inadequate cell proliferation or genomic instability. Measuring maternal TL during the periconceptional period could serve as a useful predictive biomarker for assessing the risk of fetal developmental anomalies.